False Chirality, Absolute Enantioselection and CP Violation: Pierre Curie’s Legacy - Laurence D. Barron (Magnetochemistry, 2020)
The 1884 suggestion of Pierre Curie (1859−1906) that the type of dissymmetry shown by collinear electric and magnetic fields may induce an enantiomeric excess, in a chemical reaction that would otherwise produce a racemic mixture, is explored in the context of fundamental symmetry arguments. Curie’s arrangement exhibits false chirality (time-noninvariant enantiomorphism), and so it may not induce absolute enantioselection (ae) in a process that has reached thermodynamic equilibrium, since it does not lift the degeneracy of chiral enantiomers. However, it may do so in far-from-equilibrium processes via a breakdown in microscopic reversibility analogous to that observed in elementary particle processes under the influence of CP violation, the associated force possessing false chirality with respect to CP enantiomorphism. In contrast, an influence like circularly polarized light exhibiting true chirality (time-invariant enantiomorphism) lifts the degeneracy of enantiomers, and so may induce ae in all circumstances. Although to date, ae has not been observed under the influence of Curie’s arrangement of collinear electric and magnetic fields, it is argued that two different experiments have now demonstrated ae under a falsely chiral influence in systems far from equilibrium, namely in a spinning sample under a gravitational field, and in the separation of enantiomers at a ferromagnetic surface.